Mangrove forest degradation and shoreline erosion in the Mekong delta: a case study from Ben Tre province - Kozhikkodan Veettil, Bijeesh; Ngo Xuan Quang; Nguyen Thi Kim Dung; Duong Quoc Bao; Tran Xuan-Linh; Hoang Nhat-Duc (Vietnam Journal of Science and Technology, 2022)
Viet Nam’s coastline faces many natural and human-induced threats, such as erosion, floods, sea-level changes, pollution and saltwater intrusion. Low lying deltas, such as the Mekong Delta and the Red River Delta of Viet Nam are frequently subjected to such threats. The present study investigated the degradation of mangrove forests and changes in shoreline along the coast of Ben Tre. For this purpose, we used spectral indices, such as the normalized difference vegetation index (NDVI) for mapping mangrove vegetation and the normalized difference water index (NDWI) for estimating shoreline changes. The possibilities, advantages and limitations of coastal vegetation, such as mangroves, casuarina and pandanus, as a bioshield for shoreline protection in Ben Tre coast of the Vietnamese Mekong Delta (VMD) were also discussed. The results show that coastal areas covered with newly planted mangroves showed reduced or no erosion. Currently, several hard structures have been used for short-term protection from coastal erosion in Ben Tre. For long-term coastal protection, the present study suggested an ecosystem-based adaptation using bioshield for Ben Tre coast. A combination of hard structures reinforced with bioshield is recommended for long-term and sustainable coastal protection in Ben Tre.